A robust modified model predictive control (MMPC) based on Lyapunov function for three-phase active-front-end (AFE) rectifier - Parvez M.; Mekhilef S.; Tan N.M.L.; Akagi H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Algorithms; Dynamic response; Electric rectifiers; Lyapunov functions; Lyapunov methods; Model predictive control; Power electronics; Robust control; Robustness (control systems); System stability; Ac-dc power conversion; Active front ends; Modified model; Robustness analysis; Stability analysis; Rectifying circuits